PENGARUH KUALITAS PELAYANAN DAN SOSIALISASI PAJAK TERHADAP KEPATUHAN PAJAK ( STUDI KASUS PBB-P2 UNIT PELAYANAN TEKNIS DINAS PENDAPATAN DAERAH KOTA BATAM ) - Puput Novitasari; Firdaus Hamta (Universitas Riau Kepulauan, 2017)
This study aims to determine the effect of service quality and dissemination of tax on tax compliance PBB-P2 on Dinas Pendapatan Daerah Kota Batam officer. Quality of service includes quality procedure , terms of service, clarity of service personnel, discipline of service personnel, responsible of servicr personnel, ability of service personnel, speed of service, gets justice ministry, courtesy and friendliness, the reasonableness of the service charge, suitability costs, certainty service schedules, environmental comfort and safety. Socialization includes publications, events, notifications, personal approach and the inclusion of identity, community involvement. As well as tax compliance includes the right time, arrears, criminal and audit. Respondents are Taxpayer Personal which have a NPWP and never had service experience in Dinas Pendapatan Daerah Kota Batam Office. 100 respondents predetermined with slovin method taken by accidental sampling technique. Data were collected through questionnaires and data from the internal Dinas Pendapatan Daerah Kota Batam Office, analysis tool used is regresi logistic method backward stepwise (wald ). From the analysis regresi logistic known that have a significance value below 0,005 is variable reliability and emphat. A rtinya variable quality of service and tax socialization simultaneously (synchronously) exhibited significantly impact on tax compliance in UPT PBB-P2 at Dinas Pendapatan Daerah Kota Batam.